James R. Doolittle papers - Doolittle, James R. (James Rood), 1815-1897.
Correspondence, speeches, newspaper clippings, and other papers chiefly concerning Doolittle's senate career and his work as a lawyer. Subjects include slavery, resettlement of African Americans in Africa, political reaction in the Midwest to Andrew Johnson's veto of congressional measures in 1866, the Civil War, Reconstruction, and relations between the U.S. government and American Indians. Correspondents include Thomas A. Hendricks, Samuel Phillips Lee, Hiram Paulding, Amos Reed, and William Henry Seward.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts made by Duane Mowry from originals in his possession.
Jurist and U.S. senator from Wisconsin.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hendricks, Thomas A. -- 1819-1885 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Lee, Samuel Phillips, -- 1812-1897 -- Correspondence; Paulding, Hiram, -- 1797-1878 -- Correspondence; Reed, Amos -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; African Americans -- Africa; Indians of North America -- Government relations; Reconstruction (U.S. history, 1865-1877); Slavery; Middle West -- History; United States -- History -- Civil War, 1861-1865.; Jurists; Senators, U.S. Congress -- Wisconsin